2021
DOI: 10.23887/jisd.v5i3.37069
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Preservice Elementary Teacher Ability in Creative Writing Containing Character Education with Local Wisdom Persepective

Abstract: This study aims to analyze the ability of preservice elementary teacher ability in poetry writing containing character education with local wisdom persepective. Mix method research approach is used with research design is triangulation design. The research subjects were 35 students of the elementary school teacher education program. The data were obtained through the technique of writing poetry tests and interviews. The analysis of the test used aspects of poetry writing skills. The research findings provide v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The study's findings concluded that parents who were involved with their children's problems, especially by collaborating with teachers, were more satisfied with school than parents who did not build relationships with teachers or collaborate. The use of this model will strengthen the form of collaboration that exists between counselors, teachers, and parents (Moreira et al, 2019;Winarni et al, 2021). The stages in the experiential learning model are reflective so that they can be excellent self-evaluation materials for teachers and parents to find solutions to problems faced by students (Madjar et al, 2019;Mansooreh & Mollazadeh, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study's findings concluded that parents who were involved with their children's problems, especially by collaborating with teachers, were more satisfied with school than parents who did not build relationships with teachers or collaborate. The use of this model will strengthen the form of collaboration that exists between counselors, teachers, and parents (Moreira et al, 2019;Winarni et al, 2021). The stages in the experiential learning model are reflective so that they can be excellent self-evaluation materials for teachers and parents to find solutions to problems faced by students (Madjar et al, 2019;Mansooreh & Mollazadeh, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of guidance and counseling teachers in primary schools resulted in all student problems being handled by the classroom teacher. Many cases of violence committed by elementary school students result from previously accepted behavior of teachers and parents (Winarni et al, 2021). Many parents still do not understand good parenting (Kamar et al, 2020;Wandini et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Through learning activities, students are expected to obtain information, understanding, skills, attitudes, and human values. Teachers and students participate in learning activities that shape education (Kholifah, 2020;Silvia et al, 2019;Winarni et al, 2021). The instructor must instruct, whereas the student's activity is to learn; hence, these two actors exhibit distinct behavior (Lee & Martin, 2020;Sudirman, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The experience gained by students is more memorable if the learning process obtained is the result of their own understanding and discovery. As conveyed Winarni, et al (2021), that, "people can only know what they have constructed". Therefore, in managing the teaching and learning process, teachers must choose appropriate learning methods, so that learning is more interesting and meaningful.…”
Section: Introductionmentioning
confidence: 99%